Tuberculosis vaccines: Beyond bacilli Calmette-Guérin - McShane, H (2011)
Tuberculosis (TB) disease caused by Mycobacterium tuberculosis (M. tb) remains one of the leading infectious causes of death and disease throughout the world. The only licensed vaccine, Mycobacterium bovis bacille Calmette-Gue ́rin (BCG) confers highly variable protection against pulmonary disease. An effective vaccination regimen would be the most efficient way to control the epidemic. However, BCG does confer consistent and reliable protection against disseminated disease in childhood, and most TB vaccine strategies being developed incorporate BCG to retain this protection. Cellular immunity is necessary for protection against TB and all the new vaccines in development are focused on inducing a strong and durable cellular immune response. There are two main strategies being pursued in TB vaccine development. The first is to replace BCG with an improved whole organism mycobacterial priming vaccine, which is either a recombinant BCG or an attenuated strain of M. tb. The second is to develop a subunit boosting vaccine, which is designed to be administered after BCG vaccination, and to enhance the protective efficacy of BCG. This article reviews the leading candidate vaccines in development and considers the current challenges in the field with regard to efficacy testing. © 2011 The Royal Society.